Harmonic suppression method applied to grid-connected photovoltaic inverter - ZHOU FEI; LEI TAO; LIU JINGDOU; CHEN NING; YI DI; WANG LIAN; JIA LIMIN; TONG YIBIN (2014)
The invention relates to the technical field of grid-connected photovoltaic power generation, especially to the technical field of a harmonic suppression method applied to a grid-connected photovoltaic inverter. According to the invention, suppression of harmonic current is realized, and the problem that output current of a present grid-connected photovoltaic inverter contains lots of harmonic current is solved. Acquired voltages and currents in a static three-phase coordinate system are converted to a two-phase rotating coordinate system, and active and reactive components are respectively controlled in the two-phase rotating coordinate system. An active shaft adopts a double closed-loop control strategy: an outer loop controls DC voltage and adopts a PI controller, and an inner loop controls active current and adopts a PI parallel resonance (PR) controller. A reactive shaft adopts a single closed-loop control strategy to control power factor of the grid-connected photovoltaic inverter and adopts a PI parall